Scientific Advancement in Contemporary Society: The Interface between Technology, Science and Law - Aina-Pelemo, Adetutu D.; Patil, Ananya P.; Ejembi, Paul A.; Oloketuyi, Sandra F.; T., Aina I. (European Scientific Journal, ESJ, 2019)
This article is premised on the relation of technology and applied sciences with law. The three subjects are not only interwoven but cannot be protected and regulated without the viable use of law. The unprecedented advancement ofscientific innovations has far-reaching implication in virtually all ramifications of human endeavour. Technology is an invention created using science, which needs to be sustained by prudent management and law. The research goal is to narrow down a middle ground where all these independent fields can meet and share a symbiotic relationship without stifling each other. The research seeks to ascertain the knowledge and perception of selected university students of Nigeria and India, about Science, Law and Technology. The authors adopted the doctrinal and empirical research methodology coupled with the use of cases and legislations as source of information. The research revealed that majority of the participants has knowledge about the co-existence and impact of Science, Technology and Law in the society. However, the attitude and perception of the participants constitute a fundamental influence on the degree to which technological orientations occur during learning process. Also, 85% of 200 participants agreed that there is need for frequent education and legislation as science and technology evolves in the society. Hence, this article recommends the implementation and frequent modifications of law to continually protect, encourage and ensure the societal sustainability of ethical standards.